Strange encounters: embodied others in post-coloniality - Ahmed, Sara (Routledge, 2000)
"Examining the relationship between strangers, embodiment and community, Strange Encounters challenges the assumptions that the stranger is simply anybody we do not recognize and instead proposes that he or she is socially constructed as somebody we already know. Using feminist and postcolonial theory this book examines the impact of multiculturalism and globalization on embodiment and community whilst considering the ethical and political implication of its critique for post-colonial feminism. A diverse range of texts are analyzed which produce the figure of 'the stranger', showing that it has alternatively been expelled as the origin of danger - such as in neighbourhood watch, or celebrated as the origin of difference - as in multiculturalism. The author argues that both of these standpoints are problematic as they involve 'stranger fetishism'; they assume that the stranger 'has a life of its own'". – Site de l'éditeur.
Keywords: approches et analyses; corps; cours; discipline; féminisme décolonial; histoire et politique; lit4700; philosophie; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; études culturelles

Woman: An intimate geography - Angier, Natalie (Anchor Books, 2000)
Woman is a fascinating, fact-filled guide that covers everything from organs to orgasms, hormones to hysterectomies. With her characteristic clarity, insight, and sheer exuberance of language, bestselling author Natalie Angier cuts through the still-prevalent myths and misinformation surrounding the female body, that most enigmatic of evolutionary masterpieces. With a witty and assured narrative, and a reader-friendly dose of science, Woman is an essential and engaging resource for all time.
Keywords: amériques; approches et analyses; biologie; corps; cours; différence des sexes; discipline; fem1000; médecine; premier cycle; psychologie; rapports sociaux de sexe; régions géographiques; santé; sciences; sciences humaines; stéréotypes; thématiques; états-unis

Debora et Judith : l’amour entre femmes dans l’église catholique. Et CIEL parlait, ce serait l’ENFER? - Bazinet, Colette (Recherches féministes, 2000)
Keywords: amériques; approches et analyses; compte-rendu; cours; discipline; fem1000; invisibilités; lesbianisme; premier cycle; québec; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexualité; thématiques; église

Cahiers du genre: « De la contraception à l’enfantement : l’offre technologique en question » - Béland, Bibiane (Recherches féministes, 2000)
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du sud; approches et analyses; brésil; corps; corps des femmes; cours; discipline; discours dominant; droits des femmes*; europe; france; maternité; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Heterosexuals' use of "fag" and "queer" to deride one another: a contributor to heterosexism and stigma - Burn, S M (Journal of homosexuality, 2000)
This paper is on heterosexuals' use of words such as "fag" and "queer" to refer to one another in an insulting manner. This behavior perpetuates heterosexism and the stigmatization of gays. Two hundred and fifty-seven university students (73% Euro-American) served as participants. Males exhibited more anti-gay prejudice and anti-gay behavior than females. Heterosexual males frequently used words such as "fag" and "queer" to put one another down. Anti-homosexual prejudice was predictive of anti-gay behavior. However, approximately half of those who engaged in the behavior were not strongly anti-homosexual. For these individuals, the behavior may win approval from their social group. Awareness campaigns and peer reminders that the derisive use of "fag" and "queer" harms homosexuals may be effective in changing this group. It is more difficult to reduce this behavior in individuals with strong anti-homosexual attitudes. The role of individuals and educational and work organizations in bringing about change is discussed.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; homophobie; hétérosexisme; insultes; premier cycle; psychologie; sciences humaines; soc2014; systèmes d'oppressions; thématiques

Life with the first baby: women's satisfaction with the division of roles - Cappuccini, G.; Cochrane, R. (Journal of Reproductive and Infant Psychology, 2000)
The ways parents divide their roles after their first child is born is a particularly complex arena. The success of negotiations within this close personal relationship may be central to the future of the new family. Women and their partners were surveyed in late pregnancy and 6 months after the birth. Their attitudes to role division remained largely non-traditional after the birth, even though most of them had incorporated some traditional elements into their behaviour. Emotional support received from their partners was important to women's satisfaction with role division, which had fallen only slightly after the birth. Eight of the women were interviewed in depth to explore why it might be that satisfaction with role division tended to remain high after the birth, despite the division usually not being what they had hoped for. Contributory factors may include changes in emphasis in the division of breadwinning and the maintenance of overall responsibility for traditional role areas despite sharing of tasks.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; europe; hétérosexualité; inégalités; maternité; premier cycle; privilèges; psychologie; périodes historiques; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques

Chronologie d’une émancipation. Questions féministes sur la citoyenneté des femmes - Cohen, Yolande (2000)
L’histoire des Québécoises et de leurs rapports complexes à la politique est étudiée dans ce texte à partir du prisme offert par l’analyse du phénomène des Yvettes, issu du référendum sur la souveraineté-association de 1980. Cet événement fournit l’occasion de repenser les liens qui se sont noués depuis le début du siècle entre féminin, féminisme et nationalisme. L’auteure propose une brève chronologie des principales stratégies féministes des Québécoises, qui permet de mieux appréhender les transformations politiques en cours. Elle y intègre les revendications dites sociales, qui sont souvent la raison d’être officielle des grandes organisations de femmes, comme la Fédération nationale Saint-Jean-Baptiste, les Cercles de Fermières, les AFÉAS, etc. En considérant les stratégies déployées par ces organisations pour combattre l’exclusion politique des femmes (qualifiées parfois de stratégies d’émancipation), elle identifie trois grands moments, qui sont aussi des moments clés de l’histoire politique du Québec contemporain. Au-delà de cette chronologie, qui permet de situer les lecteurs dans le contexte historique, la question de la construction politique d’une identité de genre au cours du XXe siècle est au centre de ce récit. Elle permet de comprendre comment s’est articulée la double revendication de la différence des sexes (ou la complémentarité des rôles sexués) et de l’égalité des droits, durant cette période.
Publisher: Globe, Revue internationale d’études québécoises Érudit
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; canada; cours; discipline; féminisme québécois; histoire; histoire et politique; justice sociale; militance; pol4102; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques

Les femmes, de Platon à Derrida : anthologie critique - Collin, Francoise; Pisier-Kouchner, Evelyne; Varikas, Eleni; Pisier, Évelyne; Varika, Hélène (Plon, 2000)
Cette anthologie critique propose une sélection de grands textes théoriques sur le statut des femmes. Le projet est né d'un étonnement: la place accordée à la différence des sexes est un point "aveugle" de l'enseignement de la philosophie comme de l'histoire des idées en général. Aussi nous paraît-il urgent de rendre "visibles" des textes susceptibles de nourrir une réflexion sur la différence des sexes. À l'aube du XXIe siècle, en effet, les débats qui ressurgissent sont précurseurs des transformations qui marqueront le statut des femmes et donc, aussi,celui des hommes. (4e de couverture).
Keywords: anthologie; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; histoire des femmes*; histoire et politique; lit3220; philosophie; premier cycle; rapports sociaux de sexe; savoirs; sciences humaines; thématiques

Le siècle dans la tourmente du féminisme - Daigle, Johanne (Globe : revue internationale d’études québécoises, 2000)
L’empreinte du féminisme sur le XXe siècle québécois est indélébile. De l’aube au crépuscule du siècle, la « question des femmes » a coloré les grands débats, imprégné les luttes socio-politiques et laissé sa marque sur les systèmes de lois, les institutions, l’organisation du travail et les modes de vie. Cet article veut montrer comment, dans une perspective historique, la « question des femmes » — ainsi posée par les élites masculines — fut pressentie comme l’une des grandes interrogations de ce siècle et comment les changements survenus dans la reconfiguration des rapports entre hommes et femmes — des identités sexuelles aux modèles qui les supportent — restent au coeur des enjeux d’une société.
https://www.erudit.org/en/journals/globe/2000-v3-n2-globe1497493/1000582ar/
Keywords: 1900-1999; EDI; amériques; approches et analyses; conflit; cours; discipline; discours dominant; droits des femmes*; fem1000; histoire; histoire et politique; inégalités; militance; patriarcat; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail; épistémologie

L'évidence de l'égalité des sexes : une philosophie oubliée du XVIIe siècle - Dorlin, Elsa (L'Harmattan, 2000)
Au XVIIe siècle, quatre philosophes, à quelques décennies d'intervalle, formulent en des styles très différents la thèse selon laquelle l'égalité entre les hommes et les femmes est une évidence, une vérité indiscutable. Marie de Gournay, Anna Maria Van Schurman, François Poullain de la Barre et Gabrielle Suchon, estiment que si les interdictions et les discriminations frappant les femmes perdurent, c'est que la querelle entre les défenseurs et les pourfendeurs du " Beau Sexe " est biaisée : les présupposés de la différence sexuelle rendent la question de l'égalité ou de l'inégalité des sexes indécidable.
Donné en lecture cours FEM1000: p.11-14 et 17-32
Keywords: 1600-1699; approches et analyses; cours; discipline; discours dominant; europe; fem1000; france; histoire des femmes*; histoire et politique; incontournable; inégalités; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

Femmes & art au XXe siècle: le temps des défis - Dumas, Marie-Hélène (Lunes, 2000)
Que cela soit dans les plus prestigieuses expositions ou bien dans les livres consacrés à l'art, le très faible nombre de femmes représentées ou citées - en tous les cas en France - laisse perplexe. Pourtant, les femmes ont toutes les qualités pour être reconnues comme de grands artistés. Le débat autour du statut de la <> demeure donc plus que jamais d'actualité. Cet ouvrage pose la question de la reconnaissance des femmes dans le milieu artistique tout au long du XXe siècle. Par une mise en perspective historique - car l'art n'est pas en dehors de la société - il analyse comment les femmes ont participé à la création et au développement de différents mouvements (constructivisme, dadaïsme, surréalisme, art féministe. Fluxus, ou encore le cyber-art). Il permet également de mieux comprendre les démarches d'un grand nombre d'artistes, certaines très connues comme ou Yoko Ono ou Sophie Calle, ou ne devant surtout pas être oubliées comme Hannah Höch, ou Natalia Gontcharova. Ce livre vous invite à découvrir la richesse créatrice dont ont témoigné de nombreuses femmes de tous pays tout au long du XXe siècle, mais qui demeure trop souvent invisible.
Le texte suivant : Collin, Françoise. (2000). La sortie de l’innocence, 175-189 a été donné en lecture au cours HAR4600.
Keywords: 1900-1999; arts; arts visuels et médiatiques; cours; discipline; femmes* artistes; har4600; histoire; histoire de l'art; histoire et politique; premier cycle; périodes historiques; sciences humaines; sex1911; thématiques

Sexing the body: Gender politics and the construction of sexuality - Fausto-Sterling, Anne (Basic Books, 2000)
Discusses the causes and determining factors of gender behavior differences and sexual identity, particularly biology and societal expectations, and argues that differences between male and female are not always distinct.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme matérialiste; genre; histoire et politique; hétérosexisme; injustices épistémiques; philosophie politique; premier cycle; production des savoirs; ressource en ligne; sciences humaines; sciences sociales; sex3383; sexe/genre; sexualité; sociologie; systèmes d'oppressions; thématiques; épistémologie

L'invention du naturel : les sciences et la fabrication du féminin et du masculin - Gardey, Delphine; Löwy, Ilana.. (Ed. des Archives contemporaines, 2000)
Comprendre ce que sont les hommes et les femmes, penser la différence entre les sexes a constitué et constitue encore un objet d'investigation et un enjeu politique et social de premier ordre. Des sciences d'hier à celles d'aujourd'hui, des discours et des pratiques médicales aux plus récentes sciences humaines, les auteurs de cet ouvrage révèlent la fragilité des évidences dites sur la nature ou le corps des femmes et des hommes, et insistent sur la force des arrangements et organisations du social qui ont pu en découler. Plus qu'une enquête descriptive sur les états variables des représentations proposées par les sciences, il s'agit d'analyser comment les scientifiques " en société " élaborent les critères de différenciation entre les sexes, contribuant à faire endosser à la nature certaines formes de domination. Convié à découvrir, en France et à l'étranger, l'histoire récente de ces nouveaux terrains d'enquête, le lecteur est aussi invité à méditer sur les effets de longue durée d'une modernité occidentale instaurée sous le signe de l'altérité entre raison et nature, hommes et femmes.
Textes issus de deux journées d'études qui se sont déroulées à la Cité des sciences et de l'industrie à Paris, les 24 janvier et 22 avril 1997.
Keywords: approches et analyses; cours; discipline; discours dominant; essentialisation; genre; histoire et politique; identité sexuelle; naturalisation; premier cycle; production des savoirs; rapports sociaux de sexe; sciences; sciences humaines; sciences sociales; sex3383; sexe/genre; sociologie; systèmes d'oppressions; thématiques; épistémologies féministes

Coming Out of the Castle: Gothic, Sexuality and the Limits of Language - Grove, Allen W. (Historical Reflections / Réflexions Historiques, 2000)
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; histoire; histoire et politique; identités LGBTQIA2+; lit4700; premier cycle; queer; ressource en ligne; sciences humaines; sexualité; thématiques; études littéraires

Something to tell you: the road families travel when a child is gay - Herdt, Gilbert H.; Koff, Bruce (Columbia University Press, 2000)
Even now, at the end of the twentieth century, many still have difficulty standing up and saying, "I am the parent of a gay child." Something to Tell You recounts the stories of families whose lives have been touched by the discovery that a child is lesbian or gay—how it affects and influences people's perceptions of their children and even changes the self-image of parents themselves. Focusing on fifty average families—not people seen in clinics or therapy—the authors found a consistent pattern of change: first negative, then positive. Sometimes the news led parents and siblings to form stronger bonds with the child, with each other, and with other relatives and friends. In many cases, their child's partner and partner's family grew to assume an important role in their own lives. In some cases, parents and siblings discovered new meaning in their lives through speaking out or joining PFLAG (Parents, Families, and Friends of Lesbians and Gays) and becoming part of the struggle for lesbian and gay rights. The authors found that families committed to staying together are typically able to overcome the powerful obstacles imposed by society. Something to Tell You also shows the lasting and sometimes tragic consequences for families who falter in the process of integration. Unwilling to accept their child's sexuality, some parents sought to blame each other, and all too often their own relationships unraveled as a result. Others who failed to tell close friends sometimes lost those friends through keeping secrets. Parents who neglected to form bonds with their child's partner fostered climates of alienation that persisted for years. A richly diverse collection of family stories, Something to Tell You is a book that will help break down widespread prejudice and put an end to destructive cultural myths. It affirms families' highest aspirations toward active love for their gay children, showing the steps to take toward new levels of support, solidarity, and love.
Section: xxii, 156 p. ; 24 cm.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; famille; hétérosexisme; patriarcat; premier cycle; relations familiales; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis

Sexe et genre - Mathieu, Nicole-Claude (Dictionnaire critique du féminisme, 2000)
Keywords: 1900-1999; anthropologie; approches et analyses; cours; discipline; fem1000; incontournable; outils; ouvrages de références; premier cycle; périodes historiques; rapports sociaux de sexe; sciences humaines

Expériences des femmes et théologie. La théologie « mujerista » : une nouvelle pratique théologique - Melançon, Louise (Laval théologique et philosophique, 2000)
Les théologies féministes sont plurielles de par la diversité des expériences qui leur donnent naissance. S'il est vrai que l'expérience du sexisme et de l'androcentrisme traverse les discours féministes, elle n 'en est pas moins contextuelle. La prise en compte de ces expériences des femmes en théologie interroge et commence à modifier la pratique même de la théologie. La théologie mujerista née de la survie des femmes hispano-américaines en est un exemple remarquable.
Keywords: amérique latine; amériques; approches et analyses; cours; discipline; fem1000; femmes*; intersectionnalité; inégalités; premier cycle; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexisme; systèmes d'oppressions; théologie; états-unis

Experiments in knowing: Gender and method in the social sciences - Oakley, Ann (The New Press, 2000)
Ann Oakley came to widespread attention as part of the new school of British feminists to emerge in the 1960s, and has since earned a reputation as one of the most innovative feminist thinkers and social scientists writing today. In Experiments in Knowing, a major new work, Oakley integrates her personal and professional thinking to examine the historical development of methodology in the social and natural sciences, demonstrating how both fields have been subject to a process of "gendering." Oakley not only reconciles the long-standing opposition between the quantitative and the qualitative methods but shows that the experimental and intuitive approaches must be used in tandem to provide a full understanding of any subject of scientific inquiry. Written in accessible language, Experiments in Knowing addresses themes of common interest across such diverse fields as social policy, education, health, and women's studies. Certain to generate considerable debate, it is both a fascinating history of the practice of social science from a feminist perspective, as well as an argument for a new way of thinking about our ways of knowing.
Keywords: 1900-1999; approches et analyses; cours; discipline; europe; fem1000; genre; identités LGBTQIA2+; point de vue situé; premier cycle; périodes historiques; royaume-uni; régions géographiques; sciences; sciences humaines; sciences sociales; thématiques; théories féministes; épistémologie

Questionnements féministes et méthodologie de la recherche - Ollivier, Michèle; Tremblay, Manon (L'Harmattan, 2000)
La recherche féministe repose-t-elle sur une éthique de la recherche qui lui est propre, Est-elle mieux servi par les méthodes qualitatives que quantitatives ? Comment arrive-t-elle à concilier engagement politique et effort d'élaboration d'un discours vrai sur le monde ? Cet ouvrage présente quelques éléments essentiels de la réflexion féministe actuelle sur la méthodologie de la recherche en sciences humaines et sociales.
Keywords: approches et analyses; canada; cours; cycles supérieurs; discipline; discours; fem1000; fem7000; har4600; justice sociale; méthodologie; point de vue situé; premier cycle; pédagogie; sciences humaines; sciences sociales; thématiques; épistémologie

Au sujet des corps, des techniques et des féminismes dans L'invention du naturel: les sciences et la fabrication du féminin et du masculin - Oudshoorn, Nelly (L'invention du naturel: les sciences et la fabrication du féminin et du masculin, 2000)
Section: 227 pages ; 21 cm
Keywords: 1900-1999; 1990-1999; approches et analyses; corps; cours; discipline; essentialisme; europe; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques

Manifeste contra-sexuel - Preciado, Paul B. (Balland, 2000)
Une relecture de la sexualité, à la lumière des travaux de Deleuze, Foucault, mais aussi dans la lignée du féminisme matérialiste (Wittig) et des recherches sur le genre (Butler). S'inscrivant dans une quête rétrospective d'une philosophie radicale lesbienne, l'essai se penche notamment sur le godemiché et ses différentes incarnations au sein du système patriarcal
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; lit3220; philosophie; premier cycle; queer; sciences humaines; sexualité; thématiques

Carnal appetites: food, sex, identities - Probyn, Elspeth (Routledge, 2000)
n Carnal Appetites, Elspeth Probyn charts the explosion of interest in food - from the cults that spring up around celebrity chefs, to our love/hate relationship with fast food, our fetishization of food and sex, and the impact of our modes of consumption on our identities. 'You are what you eat' the saying goes, but is the tenet truer than ever? As the range of food options proliferates in the West, our food choices become inextricably linked with our lives and lifestyles. Probyn also tackles issues that trouble society, asking questions about the nature of appetite, desire, greed and pleasure, and shedding light on subjects including: fast food, vegetarianism, food sex, cannibalism, forced feeding, and fat politics.
Keywords: approches et analyses; care; corps; cours; discipline; féminisme pop; lit4700; premier cycle; ressource en ligne; sciences humaines; sciences sociales; sexualité; thématiques; études de genres

Feminism and the body - Schiebinger, Londa (Oxford University Press, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Section: IX, 500 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme